Covalent Attachment of Carbohydrate Derivatives to an Evanescent Wave Fiber Bragg Grating Biosensor. (8th November 2009) - Stanford, Christopher J.; Ryu, Geunmin; Dagenais, Mario; Hurley, Matthew T.; Gaskell, Karen J.; DeShong, Philip
Abstract : A carbohydrate-based biosensor was prepared by functionalization of the surface of an etched fiber Bragg grating with a glucopyranosyl-siloxane conjugate. Functionalization of the surface with the conjugate resulted in a Bragg grating shift of 24 pm. This shift in the refractive index is consistent with a theoretical shift calculated assuming monolayer coverage of the glucose conjugate on the sensor. The resulting functionalized fiber was shown to interact selectively with concanavalin A (Con A), a glucose binding protein (lectin). Exposure of the glucose-functionalized fiber to peanut agglutinin, a galactosebinding lectin, did not result in a change of the refractive index corresponding to a binding event.